Building a medical research cloud in the EASI‐CLOUDS project. (20th May 2015) - Wu, Jie; Narayanan, Krishnaprasad; Nagel, Lars; Fiehe, Christoph; Litvina, Anna; Tonn, Jakob; Zoth, Carsten; Goltz, Hans‐Joachim; Unger, Steffen; Pursche, Fabian; Scheel, Michael; Brinkmann, Andre; et al.
Summary: The demand for Information Technology (IT) resources is constantly growing in the scientific area. The ability to store and process increasing amounts of data has transformed many research disciplines like the life sciences, which now rely on complex data processing and data analytics. Cloud computing can provide researchers with scalable and easy‐to‐use hardware and software resources and allows on‐demand access to services, tools, or even complete work environments. The European research project EASI‐CLOUDS has developed a service delivery platform with special regard to service integration, monitoring and management, and the negotiation of service level agreements. In order to demonstrate the capabilities of the platform, a medical‐use case was devised and implemented in close partnership with the Charité University Hospital that has a high demand for computing resources, especially in the field of magnetic resonance imaging‐related diagnostics of brain diseases. This use case can serve as a blueprint for the development of cloud‐based services for medical research. Copyright © 2015 John Wiley & Sons, Ltd.